Niqab as the Identity of Muslim Women in the Perspective of Islamic Family Law and Contemporary Social Dynamics - Wayan Paradisa Kartini; Syukri Syukri; Fikran Fikran (International Journal of Social Sciences and Humanities, 2026)
This study examines the use of the niqab as a form of Muslim women’s identity from the perspective of Islamic Family Law. The research focuses on the protection of women’s honor, family relations, and the social dynamics that emerge in contemporary society. This study employs a qualitative method using a normative-sociological approach through library research. Data were collected from primary Islamic sources, including the Qur’an and hadith, as well as Islamic jurisprudence (fiqh) literature, academic journals, and other relevant scholarly works. The findings indicate that the niqab is generally understood as part of the effort to preserve personal dignity and family honor (hifz al-‘irdh), which is one of the important objectives within the framework of maqashid al-sharia. However, its legal status remains subject to scholarly disagreement (khilafiyah), where some jurists consider it obligatory while others regard it as recommended or context-dependent. The study also reveals that the practice of wearing the niqab is influenced by various factors, including religious conviction, family expectations, cultural context, and social interaction in public spaces. Furthermore, the use of the niqab should take into account public benefit (maslahah), family harmony, and respect for women’s autonomy in making religious choices. This study concludes that the niqab is not an absolute obligation but a contextual religious practice that must be understood within the broader framework of Islamic Family Law, emphasizing balance between religious principles, social realities, and the protection of human dignity.